Ketone Incorporation Extends the Emission Properties of the Xanthene Scaffold Beyond 1000 nm. (19th November 2021) - Daly, Harrison C.; Matikonda, Siddharth S.; Steffens, Helena C.; Ruehle, Bastian; Resch‐Genger, Ute; Ivanic, Joseph; Schnermann, Martin J.
Abstract: Imaging in the shortwave‐infrared region (SWIR, λ = 1000–2500 nm) has the potential to enable deep tissue imaging with high resolution. Critical to the development of these methods is the identification of low molecular weight, biologically compatible fluorescent probes that emit beyond 1000 nm. Exchanging the bridging oxygen atom on the xanthene scaffold (C10' position) with electron withdrawing groups has been shown to lead to significant redshifts in absorbance and emission. Guided by quantum chemistry computational modeling studies, we investigated the installation of a ketone bridge at the C10' position. This simple modification extends the absorbance maxima to 860 nm and the emission beyond 1000 nm, albeit with reduced photon output. Overall, these studies demonstrate that broadly applied xanthene dyes can be extended into the SWIR range. Abstract : Installation of a ketone bridge at the C10' position of xanthene scaffold extends the absorbance maxima to 860 nm and the emission maxima beyond 1000 nm.